An insight into the coordination specificity of polyaromatic hydrocarbons (PAHs) grafted hydrazones towards rhodium(III). (1st September 2021) - Dinda, Soumitra; Naskar, Srijita; Roy, Subhadip; Pramanik, Kausikisankar; Ganguly, Sanjib
Graphical abstract: An investigation into the effect of the polyaromatic hydrocarbon and the intra-molecular π-π stacking interaction in metal–ligand bond parameters. Abstract: Upon treatment of the polyaromatic hydrocarbon (PAH) grafted hydrazones HL (1 ) with [RhCl(PPh3 )3 ], complexes of type [Rh(L)Cl2 (PPh3 )2 ] (2 ) have been isolated. The X-ray diffraction technique has been used to elucidate the structures of three complexes. The rich spectral features of the complexes in the UV–vis region have been explained by TD-DFT and their redox active nature has been validated from the well-defined responses at mild potentials as well as from a theoretical investigation of the redox orbitals. Intra-molecular π–π stacking interactions coupled with the electron withdrawing ability of the pendant PAH moiety within the ligand framework play a significant role in altering the mode of coordination (flexidentate behaviour of HL) as well as the metal–ligand bond parameters.